COVID-19 vaccination perspectives among patients with Long COVID: A qualitative study - Sarah R. MacEwan; Saurabh Rahurkar; Willi L. Tarver; Alice A. Gaughan; Laura J. Rush; Andrew Schamess; Ann Scheck McAlearney (Taylor & Francis Group, 2024)
ABSTRACTIndividuals who have Long COVID may have unique perspectives about COVID-19 vaccination due to the significant impact that COVID-19 has had on their lives. However, little is known about the specific vaccination perspectives among this patient population. The goal of our study was to improve our understanding of perspectives about COVID-19 vaccines among individuals with Long COVID. Interviews were conducted with patients receiving care at a post-COVID recovery clinic. Deductive thematic analysis was used to characterize participant perspectives according to the vaccine acceptance continuum framework, which recognizes a spectrum from vaccine acceptance to refusal. From interviews with 21 patients, we identified perspectives across the continuum of vaccine acceptance. These perspectives included acceptance of vaccines to prevent future illness, concerns about vaccine side effects on Long COVID symptoms, and refusal of vaccines due to perceived natural immunity. A limitation of our study is that these perspectives are specific to individuals receiving care at one post-COVID recovery clinic. In conclusion, our study demonstrates that some patients with Long COVID are uncertain about COVID-19 vaccines and boosters but may also be amenable to conversations that impact future vaccination acceptance. Patient perspectives should be considered when communicating recommendations for COVID-19 vaccinations to this population.